Trends in black fly density, parity and infection rates from riverside to villages of the Bafia Health District in Cameroon: implication for onchocerciasis vector control - André Domche; Hugues C. Nana-Djeunga; Philippe B. Nwane; Guy R. Njitchouang; Dirane C. Dzune-Fossouo; Betrand Nono Fesuh; Flobert Njiokou; Joseph Kamgno (Parasites & Vectors, 2023)
Abstract Background Reducing contact between humans and black flies can lead to interruption of onchocerciasis transmission. The Esperanza Window Trap (EWT) has been shown to be an effective tool for reducing black fly densities. Several shape-based improvements to this trapping system have been made to optimise its effectiveness, but optimisation of this trapping system has been based most often on the shape of the trap, collection in areas of high black fly density and the addition of attractants, without considering transmission potentials and parity rates. This study aims to investigate the differences in biting rates and transmission potential between three catch points along a transect to guide the choice of EWT placement. Methods Monthly black fly collection was carried out over a 1-year study period using the human landing method at three catch points along a transect from the riverside toward the centre of two first-line villages (Biatsota and Bayomen), in the Mbam valley in Cameroon. All female black flies caught were counted and dissected, and entomological indicators were computed and compared between the catch points and villages. Results A total of 80,732 black flies were caught, of which 57,517 were dissected; of the latter, 2743 (4.8%) were parous and 44 (1.6%) were infective. Regarding the distance to the river, a vector density gradient was observed, with the highest annual biting rates being recorded at the riverside. The highest annual transmission potentials were also recorded at the riverside (165 vs 255 infective larvae/man/year in Bayomen and Biatsota, respectively). Overall, the highest parity rates were recorded at the riverside in Biatsota (5.1%) where various human activities are frequent and at the centre of Bayomen village (6.3%). Conclusion The results of this study reveal that entomological parameters were the highest at the riverside catch sites and indicate that riverside locations should be prioritised for EWTs or other trapping systems to achieve optimal performance in onchocerciasis control. Graphical abstract